Principles of local government - Orewa, G. Oka. (Lagos : Administrative Staff College of Nigeria, 1991)
This book examines how to handle Local Government as a discipline of its own, with its own guiding principles, practical application, as well as exposing its role in the development of a nation. The book suggests ways and means of achieving the optimum in local government performance. It has fourteen chapters with concluding remarks. Each chapter deals fairly exhaustively with specific topics.
Includes index.
Includes bibliographical references (p. 240-241)
usc 15/6/17
Loans
Keywords: Local government; Local finance